Some Basic Properties of Certain New Subclass of Meromorphic Functions. (1st March 2015) - Shi, Lei; Wang, Zhi-Gang
Abstract : We introduce and investigate a new subclassℳ ( β, η ) of meromorphic functions. Some interesting properties such as inclusion relationship, coefficient estimates, neighborhoods, and partial sums are proved. Connections of the results with known results are also considered.